Adaptive fuzzy/proportion integration differentiation (PID) compound control for unbalance torque disturbance rejection of aerial inertially stabilized platform. (20th October 2016) - Zhou, Xiangyang; Li, Lingling; Jia, Yuan; Cai, Tongtong
This article describes an adaptive fuzzy/proportion integration differentiation (PID) compound control scheme to promote the disturbance rejection ability of an aerial inertially stabilized platform. To deal with the serious influence of predominant unbalance torque disturbance on the steady precision of inertially stabilized platform, dynamic modeling and simulation analysis are conducted, which reveal that the unbalance torque disturbance is nonlinear and time varying. Then, an adaptive fuzzy/PID compound controller is designed that can automatically adjust and control parameters of the system in real time. In this way, the effects of unbalance torque disturbance on control performance are suppressed greatly so that the pointing accuracy and stability are obviously improved. To validate the scheme, the simulations and experiments are conducted to a real three-axis inertially stabilized platform. The results show that under the environment of unbalance torque disturbance, the inertially stabilized platform could reach better dynamic performances by the compound scheme, leading to the high pointing accuracy and stability.